PM2.5 -AIR POLLUTION: DETERMINING FACTORS OF AIR QUALITY IN PROVINCES ON THE ISLAND OF JAVA (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
This study focuses on analysing the determining factors of particulate matter (PM2.5) air pollution in provinces on the island of Java. Air pollution is a phenomenon of environmental damage that continues to occur in line with human activities which have an impact on humans themselves, including health, global warming, and climate change. PM2.5 particulate matter pollution parameters were chosen because these micro particles easily enter through inhalation and pose a big risk to human health. Quantitative research methods were employed to make sense of the available secondary data. Econometric models-Panel Data Regression Analysis were used to examine the sources causing air pollution-PM2.5. The results showed that population density and manufacturing industrial production were important factors in increasing air pollution-PM2.5. This can be explained by the fact that population density creates complexity in handling garbage and household waste which has the potential to increase emissions, while the manufacturing industry is associated with industrial waste and factory chimney smoke which directly pollutes the air. This research is useful for strengthening control policies and mitigation efforts for air pollution that is harmful to the environment and human health more effectively. Therefore, controlling emission sources and disturbances is necessary to prevent air quality degradation caused by these sectors.
Keywords: PM2.5; Real GRDP; manufacturing industrial production; population density